IMPLEMENTATION OF A WEB-BASED REAL-TIME MONITORING SYSTEM FOR VIBRATION, TEMPERATURE, AND NOISE OF REFRIGERATION MACHINES WITH MICROCONTROL - Demeianto, Bobby; Arafat, Yasser; Hermawan, Ade; Nurita, Yani; Abrori, M. Zaki Latif; Idrus, Muhamad Amril; Marsono, Marsono (Politeknik Kelautan dan Perikanan Dumai, 2025)
Real-time monitoring of vibration, temperature, and noise in refrigeration machines using microcontrollers is still rarely discussed, although it plays a crucial role in maintaining machine performance and supporting decision-making for predictive maintenance. This research aims to design and implement a microcontroller-based monitoring system capable of measuring and recording machine operational parameters in real-time with adequate accuracy. The system uses an accelerometer sensor for vibration detection, an infrared thermometer for temperature measurement, and an electret microphone for noise monitoring. The data is processed by a microcontroller equipped with an SD card module for storage and a WiFi connection for remote access via the web. The test results show that this device can detect changes in vibration with an Mean Absolute Error value of 0.34 m/s², temperature with a Mean Absolute Percentage Error value of 1.35%, and provides real-time data that can be accessed wirelessly through other devices connected to the WiFi network. The contribution of this research lies in providing a monitoring solution that improves operational efficiency, minimizes the risk of downtime, and supports the optimal management and maintenance of refrigeration machines.